2023
DOI: 10.1101/2023.06.21.546009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A transient protein folding response targets aggregation in the early phase of TDP-43-mediated disease

Rebecca San Gil,
Dana Pascovici,
Juliana Venturato
et al.

Abstract: Understanding the mechanisms that drive TDP-43 pathology is integral to combating neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). To address this, we sought to determine the timeline of proteomic alterations across disease course in TDP-43 proteinopathy. Using longitudinal quantitative proteomics analysis of cortex samples from the cytoplasmic TDP-43 rNLS8 mouse model of ALS and FTLD, we identified several distinct protein subsets characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Formaldehyde crosslinking and homogenization of brain tissue was adapted from previous protocols (Liu-Yesucevitz et al, 2010;San Gil et al, 2024;Sap et al, 2021). 500 µl of 0.5% formaldehyde in PBS was added to 30 mg of frozen mouse brain tissue, previously crushed under N 2 and placed on a rotating wheel for 10 mins at room temperature.…”
Section: Formaldehyde Crosslinking and Tissue Lysismentioning
confidence: 99%
See 2 more Smart Citations
“…Formaldehyde crosslinking and homogenization of brain tissue was adapted from previous protocols (Liu-Yesucevitz et al, 2010;San Gil et al, 2024;Sap et al, 2021). 500 µl of 0.5% formaldehyde in PBS was added to 30 mg of frozen mouse brain tissue, previously crushed under N 2 and placed on a rotating wheel for 10 mins at room temperature.…”
Section: Formaldehyde Crosslinking and Tissue Lysismentioning
confidence: 99%
“…These studies identified multiple disease-related changes in biological pathways. However, these analyses were performed using soluble protein fractions (Lee et al, 2023;San Gil et al, 2024) without TDP-43 immunoprecipitation, and would therefore not accurately capture the TDP-43-associated SG proteome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation